Anomalous tunneling of phonon excitations between two bose-einstein condensates - Kagan, Y; Kovrizhin, D; Maksimov, L (American Physical Society, 2003)
We discuss the tunneling of phonon excitations across a potential barrier separating two condensates. It is shown that a strong barrier proves to be transparent for the excitations at low energy ε. Moreover, the transmission is reduced with increasing ε in contrast to the standard dependence. This anomalous behavior is due to the existence of a quasiresonance interaction. The origin of this interaction is a result of the formation of a special well determined by the density distribution of the condensate in the vicinity of a high barrier.